2019
DOI: 10.15832/ankutbd.426252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregelatinization and Retrogradation on Some Physicochemical Changes of Wheat-Potato Starches

Abstract: The freezable (FW) and unfreezable water (UFW) contents of wheat and potato starches and their physically modified forms [pregelatinized (PGS) and retrograded (RS)] were analyzed by Differential Scanning Calorimetry (DSC) at various hydration levels (25, 35, 45, 55, 65, 75 and 85%). In all the starch samples, the UFW content increased with increasing hydration level. Potato starch samples (native, pregelatinized and retrograded) had higher UFW contents than wheat starch samples at all hydration levels. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…12 Lebesi et al reported that treatment of oat bran with enzymes such as CE, ⊍-amylase and glucoamylase resulted in an increase of total phenolic and antioxidant activity of oat bran. 13 PG and enzymatic hydrolysis have been widely used in food processing, 14,15 but not much in rice wine production. Therefore, to understand the effect and its mechanism of PG and CE addition on the fermentation process of BRW, we investigated the effects of PG and CE on the properties of black rice and the physicochemical properties of fermented mash, exploring the effects on the free amino acids (FAAs), volatile flavor substances, active substances and antioxidant activities of BRW.…”
Section: Introductionmentioning
confidence: 99%
“…12 Lebesi et al reported that treatment of oat bran with enzymes such as CE, ⊍-amylase and glucoamylase resulted in an increase of total phenolic and antioxidant activity of oat bran. 13 PG and enzymatic hydrolysis have been widely used in food processing, 14,15 but not much in rice wine production. Therefore, to understand the effect and its mechanism of PG and CE addition on the fermentation process of BRW, we investigated the effects of PG and CE on the properties of black rice and the physicochemical properties of fermented mash, exploring the effects on the free amino acids (FAAs), volatile flavor substances, active substances and antioxidant activities of BRW.…”
Section: Introductionmentioning
confidence: 99%
“…The solution to the problem of ensuring the stability of disperse systems is facilitated by the introduction of thickeners that bind the liquid and increase the viscosity of the system. For example, starches, which can be native or modified [3,4].…”
Section: Introductionmentioning
confidence: 99%